Paving the way for the use acid-resistant proteins to control dental caries through acquired pellicle and dental biofilm microbiome engineering: proof-of-concept in vitro and in vivo studies - Araujo, Tamara Teodoro (2024)
This study evaluated, in vivo: 1) changes in the protein composition of acquired enamel pellicle (AEP) formed after 3 or 120 min following treatment with sugarcane-derived cystatin (CaneCPI-5), statherin-derived peptide (StN15), hemoglobin (Hb), or a combination of the three proteins (Comb); 2) changes in the initial colonizers of enamel biofilm formed after 3 h following treatments with the protein solutions; and in vitro 3) analyzed modifications in the microcosm biofilm through metabolic activity, Colony-Forming Units (CFU) count, and enamel demineralization after treatment with different concentrations of CaneCPI-5, StN15, and Hb, individually or in combination. Ten volunteers participated in the in vivo study, following a crossover protocol consisting of two independent experiments. In each phase, after prophylaxis, rinses were performed with different solutions. AEP formation occurred after 3 and 120 min, and it was analyzed using label free quantitative proteomics. The biofilm was formed for 3-h after rinse with the solutions. Biofilm samples underwent 16S rRNA gene sequencing by Next Generation Sequence (NGS). In the in vitro study, a microcosm biofilm protocol involving 474 samples of bovine enamel was used. Proteins were tested at different concentrations, and the analyses included resazurin, CFU, and transverse microradiography (TMR). Proteomic analysis of the 3-min AEP revealed that all groups, when compared to the control, were effective in increasing the quantity of proteins and the diversity of the protein profile. In all groups, an increase in non-typical AEP proteins with functions related to calcium, iron, and hydroxyapatite binding was observed, suggesting that these proteins/peptides may recruit protective proteins with yet unknown functions in AEP. On the other hand, in the 120-min AEP, a significant increase in acid-resistant, antibacterial, immune response, cell adhesion, and proteins directly interacting with bacterial adhesins was observed. The microbiome showed an increase in commensal bacteria in all groups compared to the control, as well as a reduction in the abundance of acid-tolerant bacteria: Veillonella, Actinomyces (Hb and Comb), Streptococcus (except Comb), and Prevotella compared to the control. The antibacterial and anticaries potential of the solutions showed that only Comb was not effective in reducing metabolic activity and CFU count. On the other hand, all individual or combined solutions reduced enamel demineralization. The results indicate that the modification of AEP by incorporating isolated or combined proteins/peptides altered the subsequent layers of the pellicle, affecting the initial bacterial adhesion process, with a consequent increase in beneficial bacteria abundance and a reduction in pathogenic species. In addition, all solutions were able to decrease in vitro dental demineralization. Thus, these results highlight, for the first time, the potential use of these proteins/peptides to control caries through the engineering of acquired enamel pellicle and dental biofilm microbiome.